A travel in the narrative turn of the consciousness of a diaspora ghost in The Hounding of David Oluwale. Issue 2 (1st October 2017) - Ojoniyi, Olabode Wale
There is a sense in which African Diasporic contemporary narrative-centred drama helps in the reconceptualization of images, identity and the perception of 'self' against the 'others' within the totality of the experiences of the individual that form the sum of his/her consciousness. And, if we agree with Jean-Paul Sartre that consciousness is intentionality, it means that such images, identity, conceptualization and perception are prompts for narrative performance action and counter-action. In essence, narrative consciousness is not a mere dormant awareness and recreation of a state of being; it is perhaps an agent provocateur of crisis that often motivates characters to destructive actions. This is what we see in the recreation of Oluwole's life in The Hounding of David Oluwale. The tragic end of Oluwole appears to have a link to the consciousness of his black 'self' against that of the white 'others', and this seems to, even now, underscore the uneasy life of the new African Diasporas in their host communities. It appears that there is an inherently sustained overt and covert conflict in the relationship between the Diasporas and their host. It is for this reason that one feels that the understanding of the narrative consciousness of the playwright and that of the characters in the play in existential dialectical terms is necessary as we continue to engage with the challenges of the life of the African Diasporas. This article, therefore, analyses the consciousness of the African Diaspora 'selves' against the 'others' of their hosts as reflected in the play.